Professional Teaching and Learning Effectiveness: A Case of English Language Teaching in Indonesia - Bachtiar, Bachtiar (International Journal of Education, 2021)
This study aims to find out the effectiveness of teacher professional learning (PL) as an effort to increase English language teaching quality in South Sulawesi, Indonesia. It used descriptive qualitative and quantitative case study approach to find about the continuous learning and development activities. Data were derived from questionnaire, observation, and semi-structured interviews. The results revealed that in-service training program is considered effective for sharing knowledge, skills and information among English language teachers. The findings also revealed that Information and Communication Technology (ICT) should be learned in-depth during professional learning activities. In addition, the respondents perceived Subject Teacher’s Meeting or teacher study groups as an effective collaborative model of professional learning activities. This study suggests that the need to involve English language teachers in a training at least once a year as an effort to help them gain new insight and experience in the acquisition of new knowledge and skills and to experience in solving problems both at school and outside school.